The role of co-occurring obesity in the association between lumbar disc degeneration and disability related to low back pain - Mertimo, Teija; Oura, Petteri; Karppinen, Jaro; Niinimäki, Jaakko; Blanco Sequeiros, Roberto; Määttä, Juhani; Kankaanpää, Markku; Heikkala, Eveliina (BioMed Central, 2026)
Background
Low back pain (LBP) and obesity-related diseases cause a significant burden to both individuals and societies. Although not confirmed by all studies, a significant association has been found between lumbar disc degeneration (LDD) and LBP. The role of obesity in this association is not known. Our aim was to investigate whether obesity, measured by different indicators, modifies the association between LDD and LBP-related disability.
Methods
A total of 1080 individuals who had experienced LBP during the previous year responded to questionnaires, participated in a clinical examination, and underwent 1.5-T lumbar magnetic resonance imaging at the age of 47. Full data were available for 842 individuals. LBP-related disability (numerical rating scale, range 0–10) was assessed as the outcome. LDD was evaluated by a Pfirrmann-based sum score (range 0–15) and was assessed as the exposure. As regards outcome and exposure, higher values reflected a greater disability or LDD burden, respectively. The role of obesity (according to five different anthropometric indicators) in the association between the LDD sum score and LBP-related disability was analysed using general linear regression models stratified by the presence of obesity. Adjustments were made for sex, smoking, education, leisure-time physical activity, occupational physical exposure, Modic changes and disc herniations.
Results
A significant positive association between LDD and LBP-related disability was observed among the individuals without obesity, regardless of the anthropometric indicator used: body mass index (adjusted beta [ß] = 0.119, 95% confidence interval [Cl] = 0.030–0.208, p = 0.009), waist circumference (0.134, 0.038–0.231, p = 0.007), body fat percentage (0.187, 0.091–0.283, p < 0.001), waist-to-height ratio (0.149, 0.064–0.235, p < 0.001), and waist-to-hip ratio (0.171, 0.067–0.275, p = 0.001). No significant associations were detected between LDD and LBP-related disability among the individuals with obesity.
Conclusions
LDD is associated with LBP-related disability among individuals without obesity but not among those with obesity. Although this cross-sectional study cannot establish causality, the findings suggest that LBP-related disability may be related also to factors other than LDD burden among individuals with obesity. This study adds to the evidence that obesity may modify the association between LDD and LBP-related disability.